2002
DOI: 10.1093/alcalc/37.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Consumption on Eight Circulating Markers of Liver Fibrosis

Abstract: A number of circulating breakdown products of collagen or other components of extracellular matrix, matrix degrading metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) have been proposed as markers of hepatic fibrosis. However, the published results lack consistency. Since many of the patients with fibrosis studied were alcoholics, the question was raised whether recent alcohol consumption may affect the results obtained. Using sandwich-type assays of radioimmunoassay technology with corresponding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…We have shown that chronic alcohol consumption may affect the levels of some of these fibrosis markers (Nouchi et al, 1987;Ponomarenko et al, 2002). Moreover alcohol metabolism itself can contribute to the posttranslational modification of these proteins, altering their representation in the blood stream and therefore their significance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown that chronic alcohol consumption may affect the levels of some of these fibrosis markers (Nouchi et al, 1987;Ponomarenko et al, 2002). Moreover alcohol metabolism itself can contribute to the posttranslational modification of these proteins, altering their representation in the blood stream and therefore their significance.…”
Section: Discussionmentioning
confidence: 97%
“…In an early study (Nouchi et al, 1987) we have shown that PIIINP and laminin as well as some other markers (Ponomarenko et al, 2002) may be affected by acute alcohol intoxication and its withdrawal; this factor was usually not taken into account and might have affected some of the results published before. Moreover, laminin, a major noncollagenous glycoprotein of basement membrane was found to be elevated in alcoholic hepatitis and cirrhosis (Nouchi et al, 1987) and increased hepatic levels were later demonstrated in alcoholic liver disease (Niemela¨et al, 1990).…”
mentioning
confidence: 99%
“…Moreover, active alcohol consumption does not seem to affect the concentration of TIMP-1. This is important in populations including patients with alcoholic liver disease, but new prospective studies are needed to totally rule out an acute effect of alcohol on TIMP-1 levels in cirrhosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although various serum markers, such as ␥-GTP (17), carbohydrate-deficient transferrin (17,18), metalloproteinase-9 (19,20), tissue polypeptide-specific antigen (21), type 4 collagen (22), laminin (20), hyaluronic acid (23), and CYP2E1 activity (24), have been introduced for the evaluation of alcohol consumption and ALD, it has remained unclear which is the best marker.…”
Section: Discussionmentioning
confidence: 99%